Jua Basambuik Pohon Kelapa Ditinjau Dari Hukum Islam - Afif, Rifqul; Yunimar (El-kahfi | Jurnal Ekonomi Islam, 2022)
This research is a qualitative research, after the data is collected, the data is processed and analyzed by re-examining the data obtained in each question according to the problem being studied, describing what is obtained from the research results, and conclusions that conclude the data to answer each of the overall problems. researched. Based on the results of the analysis obtained, it was concluded that the implementation of coconut tree basambuik in Nagari Gunung Padang Alai was canceled because the pillars and conditions of ijarah were not fulfilled. The pillars and conditions that are not fulfilled are: first, the benefits that are the object of the ijarah must be fully known so that there will be no disputes in the future, both in terms of the type, nature and conditions of the goods to be rented or the work to be carried out. Second, sighat in the contract is very important because it is from the clarity of sighat that it becomes an understanding of the implementation of the ijarah, because sighat is a form of agreement from both parties to carry out the ijarah. Meanwhile, in the implementation of sighat coconut tree basambuik carried out by land owners and tenants it is not clear, the existence of gharar, namely uncertainty about the consequences of a case/transaction or, ambiguity between good and bad.